A 2‐year prospective case series on volumetric changes, PROMs, and clinical outcomes following sinus floor elevation using deproteinized bovine bone mineral as filling material. (11th February 2019) - Younes, Faris; Cosyn, Jan; De Bruyckere, Thomas; Cleymaet, Robbert; Eghbali, Aryan
Abstract: Background: A sinus floor augmentation may be indicated when a lack of hard tissue impedes implant placement. Although clinically successful, evidence supporting the long‐term three‐dimensional stability of the grafted volume is scarce. Second, evidence on the patient's acceptance of this type of treatment is limited. Purpose: First is to evaluate the changes in graft volume after lateral wall sinus lifting based on superimposed cone beam computed tomography (CBCT) images and then to assess patient‐reported outcome measures (PROMs) and clinical outcomes. Materials and Methods: Partially edentulous patients in need of a sinus lift and fixed reconstruction on at least two neighboring implants were selected for a prospective case series. Lateral wall sinus augmentation was performed using deproteinized bovine bone mineral (DBBM) as the only filling material. Volumetric changes were quantified on the basis of a preoperative CBCT and three postoperative CBCTs (at 2 weeks, 3 months, and 2 years). PROMs and clinical parameters were registered. Results: Twenty‐two patients (7 males, 15 females; mean age 59 years) participated of which three patients dropped out during the follow up. Graft volumes amounted to 1418.26 mm 3 at 2 weeks, 1201.21 mm 3 at 3 months, and 1130.13 mm 3 at 2 years postoperative pointing to a relative graft volume stability of 79.7%. Swelling was the leading symptom during the first week. A peak in visual analogue scale scores was observed for pain, swelling, and hematoma the day of surgery and 1 day postoperation with a statistically significant decline between days 3 and 7. Hemorrhage and nose bleeding occurred in 18.2% and 27.3% of the subjects, respectively. About 95.5% of the subjects would undergo the treatment again. All implants integrated successfully and demonstrated healthy clinical conditions. Conclusion: Lateral wall sinus augmentation using DBBM as the only filling material is a viable treatment concept given limited graft resorption, good patients' tolerance, and clinical outcomes.